Biodegradable laminate and molded article
Patent Information
- Application Number
- JP2023135547
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-08-23
AI Technical Summary
【0014】 本発明によれば、無機物質粉末を多量に含んでいても、所望の分解速度に調整することができる生分解性積層体及び成形体を提供することができる。
Smart Images

Figure 2025030337000001 
Figure 2025030337000002 
Figure 2025030337000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a biodegradable laminate and a molded article. [Background technology]
[0002] Conventionally, general-purpose resins have been used as materials for packaging, agricultural materials, civil engineering and construction materials, etc. In recent years, the use of biodegradable resins has been considered as materials with less environmental impact.
[0003] It is desirable for a molded article containing a biodegradable resin to maintain its shape during use and to be rapidly biodegraded after use. For example, in the case of agricultural mulch films and seedling pots, it is desirable for the shape and strength to be maintained at least until the crops grow to a certain extent, and then for the molded article to be rapidly decomposed. Therefore, it is desirable to be able to adjust the decomposition rate of a molded article containing a biodegradable resin according to the application.
[0004] In response to this, various laminate sheets have been proposed that contain biodegradable resins for use in the above-mentioned molded bodies, and in which the decomposition rate of each layer is adjusted by using biodegradable resins having different decomposition rates for each layer or by adding additives to each layer to adjust the decomposition rate.
[0005] For example, Patent Document 1 discloses a laminate sheet made of a biodegradable resin, the laminate sheet having a first layer containing a first additive such as a hydrolysis inhibitor and a second layer containing a second additive such as a hydrolysis promoter. Patent Document 2 discloses a laminate sheet having a layer containing a biodegradable resin with a slow decomposition rate. Patent Document 3 discloses a laminate sheet having a three-layer structure with an inner layer and outer layers disposed on both sides of the inner layer, in which the biodegradation rate is changed by changing the mixing ratio of the aliphatic polyester and poly-3-hydroxybutyric acid in each layer.
[0006] Patent Document 4 also discloses a seedling pot having an inner layer of a biodegradable resin with a slow decomposition rate and an outer layer of a biodegradable resin with a fast decomposition rate. Patent Document 5 discloses a seedling pot having a layer made of a biodegradable resin and layers on both sides of the layer made of a composition in which a biodegradable resin is mixed with a biodegradation promoter such as cellulose powder.
[0007] In recent years, the use of materials in which a large amount (30% by mass or more) of inorganic powder has been added to biodegradable resins has been considered as environmentally friendly materials that reduce the amount of resin used and further reduce the environmental burden. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2012-205552 A [Patent Document 2] JP 2002-219779 A [Patent Document 3] JP 2000-129105 A [Patent Document 4] Japanese Patent Application Publication No. 9-98671 [Patent Document 5] JP 2006-217442 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, it has sometimes been difficult to adjust the decomposition rate of molded articles made of a material in which a large amount of inorganic powder has been added to a biodegradable resin, compared to molded articles that do not contain inorganic powder.
[0010] For example, the above-mentioned molded body is obtained through a process of melt-kneading and compounding a biodegradable resin with a large amount of inorganic powder. The presence of a large amount of inorganic powder during this melt-kneading tends to increase the viscosity of the kneaded product, and large torque and heat are likely to be generated. The hydrolysis rate of the biodegradable resin may differ from that expected due to the influence of such torque and heat.
[0011] When such a molded article is used as, for example, a seedling pot, if the decomposition rate cannot be appropriately adjusted, the laminate may decompose faster than expected and may not function as a seedling pot. On the other hand, if the decomposition rate is too slow, the decomposition of the material may not progress even after the seedling pot is placed in soil, which may hinder the growth of seedlings.
[0012] The present invention has been made in consideration of the above circumstances, and aims to provide a biodegradable laminate and molded body that can be adjusted to a desired decomposition rate even when it contains a large amount of inorganic substance powder. [Means for solving the problem]
[0013] [1] A biodegradable laminate having a first layer and a second layer, each of the first layer and the second layer containing a biodegradable resin and an inorganic powder in a mass ratio of 70:30 to 10:90, the first layer further containing 0.1% by mass or more and 5.0% by mass or less of one or more first additives selected from the group consisting of glycerol acetate fatty acid esters and acetyl tributyl citrate, and the second layer further containing 0.1% by mass or more and 5.0% by mass or less of one or more second additives selected from the group consisting of isocyanate compounds, epoxy compounds, and carbodiimide compounds. [2] The biodegradable laminate according to [1], wherein each of the first layer and the second layer contains the biodegradable resin and the inorganic substance powder in a mass ratio of 70:30 to 30:70. [3] The biodegradable laminate according to [1] or [2], wherein the biodegradable resin comprises one or more biodegradable resins selected from the group consisting of polylactic acid, polyhydroxybutyrate, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), polycaprolactone, polybutylene succinate, polyethylene succinate, polymalic acid, polyglycolic acid, polydioxanone, poly(2-oxetanone), polybutylene adipate terephthalate (PBAT), and polybutylene succinate adipate (PBSA). [4] The biodegradable laminate according to any one of [1] to [3], wherein the biodegradable resin includes a biodegradable resin having a melting point of 170° C. or lower. [5] The biodegradable laminate according to any one of [1] to [4], wherein the inorganic substance powder contains ground calcium carbonate powder. [6] The biodegradable laminate according to [5], wherein the average particle size of the ground calcium carbonate powder is 0.7 μm or more and 6.0 μm or less. [7] A molded article comprising the biodegradable laminate according to any one of [1] to [6]. [8] The molded body according to [7], wherein the molded body is an agricultural mulch film with one side in contact with soil, and the first layer is disposed on the side in contact with the soil. [9] The molded body described in [7], wherein the molded body is a seedling pot, bag or bottle, and the second layer is arranged on the inside of the molded body and the first layer is arranged on the outside of the molded body. Effect of the Invention
[0014] According to the present invention, it is possible to provide a biodegradable laminate and a molded article, the decomposition rate of which can be adjusted to a desired value even if the biodegradable laminate and molded article contain a large amount of inorganic substance powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] A common method for adjusting the decomposition rate of a laminate is to combine multiple layers made of different types of base biodegradable resins (see Patent Documents 2 and 3). However, depending on the combination of biodegradable resins, physical properties such as elongation may differ significantly, and the laminate may not function. Therefore, it is desirable to be able to adjust the decomposition rate to a desired level even if the base biodegradable resin is the same type.
[0016] As a result of intensive research, the inventors have found that by laminating a first layer containing a predetermined amount of one or more selected from the group consisting of glycerin acetate fatty acid esters and acetyl tributyl citrate as a first additive, and a second layer containing one or more selected from the group consisting of isocyanate compounds, epoxy compounds and carbodiimide compounds as a second additive, the decomposition rate can be adjusted to a desired level even in a laminate of a resin composition containing a large amount of inorganic substance powder.
[0017] The mechanism is unclear, but is speculated as follows. The first additive, glycerin acetate fatty acid ester and acetyl tributyl citrate, are easily decomposed during compounding and tend to generate free carboxylic acids. The generated free carboxylic acids can promote hydrolysis of the biodegradable resin. In other words, the first additive can function as a component that promotes hydrolysis.
[0018] On the other hand, the isocyanate group, epoxy group, and carbodiimide group of the second additive, the isocyanate compound, the epoxy compound, and the carbodiimide compound, are highly reactive with carboxyl groups. Therefore, these components are likely to react with free carboxylic acid generated by hydrolysis of the biodegradable resin during compounding, and can suppress further progress of hydrolysis of the biodegradable resin. In other words, the second additive can function as a component that suppresses hydrolysis.
[0019] In this way, by arbitrarily laminating a layer containing a first additive and having a fast decomposition rate with a layer containing a second additive and having a slow decomposition rate, the decomposition rate of the entire laminate can be appropriately adjusted depending on the application.
[0020] Hereinafter, a biodegradable laminate according to one embodiment of the present invention and a molded article containing the same will be specifically described.
[0021] 1. Biodegradable laminate A biodegradable laminate according to one embodiment of the present invention includes a first layer and a second layer.
[0022] 1-1. First layer The first layer includes a biodegradable resin, an inorganic powder, and one or more additives selected from the group consisting of glycerol acetate fatty acid ester and acetyl tributyl citrate as a first additive. Such a first layer has a slower decomposition rate than the second layer.
[0023] 1-1-1. Biodegradable resin As the biodegradable resin, any biodegradable resin can be used. Examples of biodegradable resins include: Aliphatic polyester resins such as polylactic acid (PLA), polyhydroxybutyrate, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), polycaprolactone, polybutylene succinate (PBS), polyethylene succinate (PBA), polymalic acid, polyglycolic acid (PGA), polydioxanone, poly(2-oxetanone), polybutylene succinate adipate (PBSA); Aliphatic-aromatic copolymer polyester resins such as polybutylene terephthalate / succinate (PETS), polybutylene adipate terephthalate (PBAT), and polytetramethylene adipate / terephthalate; Included are mixtures of natural polymers such as starch, cellulose, chitin, chitosan, gluten, gelatin, zein, soy protein, collagen, and keratin with the above-mentioned aliphatic polyester resins or aliphatic aromatic copolyester resins.
[0024] Among these, from the viewpoint of exhibiting good biodegradability and moldability, the biodegradable resin preferably contains an aliphatic polyester resin or an aliphatic aromatic copolymer polyester resin, and more preferably contains one or more selected from the group consisting of polylactic acid, polyhydroxybutyrate, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), polycaprolactone, polybutylene succinate, polyethylene succinate, polymalic acid, polyglycolic acid, polydioxanone, poly(2-oxetanone), polybutylene succinate adipate, and polybutylene adipate terephthalate. Note that polylactic acid includes both a homopolymer of lactic acid and a copolymer of lactic acid and another copolymerization monomer.
[0025] In order to further improve the moldability and flexibility of the laminate, it is preferable to include a biodegradable resin having a melting point of 170° C. or less, preferably 60° C. or more and 140° C. or less. Such biodegradable resins are particularly susceptible to damage during compounding. In a biodegradable laminate containing such a biodegradable resin, the adjustment of the decomposition rate by the first layer and the second layer described above becomes more effective.
[0026] The melting point of the biodegradable resin can be measured by the following method. Using a differential scanning calorimeter, a resin sample is heated in a nitrogen stream from 20° C. to 190° C. at a rate of 10° C. / min to melt the sample, thereby obtaining a crystalline melting curve. In the obtained crystalline melting curve, the top temperature of the melting point peak on the highest temperature side can be determined as the melting point Tm.
[0027] The biodegradable resin contained in the first layer may be one type, or two or more types may be combined.
[0028] The content of the biodegradable resin in the first layer is not particularly limited as long as the content ratio of the biodegradable resin to the inorganic substance powder satisfies the range described below. The lower limit of the content of the biodegradable resin is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, relative to the first layer. When the content of the biodegradable resin is 10% by mass or more, moldability can be further improved. On the other hand, the upper limit of the content of the biodegradable resin is preferably 70% by mass or less, more preferably 60% by mass or less. When the content of the biodegradable resin is 70% by mass or less, the content ratio of the inorganic substance powder is higher, so that not only can the manufacturing cost be further reduced, but also the mechanical strength can be further increased.
[0029] 1-1-2.Inorganic substance powder As the inorganic powder, any inorganic powder can be used. Examples of the inorganic powder include carbonates, sulfates, silicates, phosphates, or borates of metals such as calcium, magnesium, aluminum, titanium, iron, and zinc; oxides of the above metals; and hydrates of the above salts or oxides.
[0030] Specific examples of inorganic substance powders include calcium carbonate, magnesium carbonate, zinc oxide, titanium oxide, silica, alumina, clay, talc, kaolin, aluminum hydroxide, magnesium hydroxide, aluminum silicate, magnesium silicate, calcium silicate, aluminum sulfate, magnesium sulfate, calcium sulfate, magnesium phosphate, barium sulfate, silica sand, carbon black, zeolite, molybdenum, diatomaceous earth, sericite, shirasu, calcium sulfite, sodium sulfate, potassium titanate, bentonite, graphite, etc. The inorganic substance powder contained in the first layer may be one type, or two or more types may be combined.
[0031] Among these, calcium carbonate powder is preferable, since calcium carbonate powder can not only increase the mechanical strength of the resulting molded body but also reduce the production cost.
[0032] The calcium carbonate powder may be heavy calcium carbonate powder or light calcium carbonate powder. Heavy calcium carbonate is calcium carbonate (CaCO 3 Precipitated calcium carbonate is calcium carbonate obtained by mechanically pulverizing natural raw materials (such as limestone) that mainly contain calcium carbonate. Precipitated calcium carbonate is calcium carbonate prepared by a synthetic method (such as a chemical precipitation reaction). From the viewpoint of further increasing compatibility with biodegradable resins, it is preferable that the inorganic substance powder contains heavy calcium carbonate powder.
[0033] The inorganic powder may be treated with a surface treatment agent. As the surface treatment agent, a surface treatment agent containing sulfonic acid, a surface treatment agent containing a sulfonate, or a surface treatment agent containing a phosphate is preferable from the viewpoint of improving the dispersibility of the inorganic powder.
[0034] The shape of the inorganic powder is not particularly limited and may be any of particles, flakes, granules, and fibers. The particles include spherical and irregular shapes.
[0035] The average particle size of the inorganic powder based on the air permeability method according to JIS M-8511 is preferably 0.7 μm or more and 6.0 μm or less, more preferably 1.0 μm or more and 5.0 μm or less. When the average particle size of the inorganic powder is 0.7 μm or more, the dispersibility in the biodegradable resin can be further improved. When the average particle size of the inorganic powder is 6.0 μm or less, the deterioration of the appearance due to the unevenness of the surface of the laminate can be suppressed.
[0036] The average particle size of the inorganic powder can be calculated from the results of measuring the specific surface area by the air permeability method in accordance with JIS M-8511. As a measuring device, for example, a specific surface area measuring device SS-100 manufactured by Shimadzu Corporation can be used.
[0037] The lower limit of the content of the inorganic substance powder in the first layer is not particularly limited, but is preferably 30% by mass or more, more preferably 40% by mass or more, relative to the first layer. When the content of the inorganic substance powder is 30% by mass or more, the mechanical strength of the biodegradable laminate can be further increased and the manufacturing cost can be further reduced. In addition, the torque during kneading is also increased, so the biodegradation rate of the first layer is likely to be faster. The upper limit of the content of the inorganic substance powder is preferably 90% by mass or less, more preferably 80% by mass or less. When the content of the inorganic substance powder is 90% by mass or less, the content ratio of the biodegradable resin is a predetermined amount or more, so that moldability is less likely to be impaired.
[0038] The mass ratio of the biodegradable resin to the inorganic substance powder contained in the first layer (biodegradable resin:inorganic substance powder) is 70:30 to 10:90, preferably 70:30 to 30:70, and more preferably 60:40 to 40:60. The higher the mass ratio of the inorganic substance powder, the higher the mechanical strength of the biodegradable laminate tends to be. Also, the decomposition rate of the biodegradable resin tends to be faster. The lower the mass ratio of the inorganic substance powder, the higher the moldability tends to be.
[0039] 1-1-3. First additive The first additive is one or more selected from the group consisting of glycerol acetate fatty acid ester and acetyl tributyl citrate. These components not only function well as plasticizers to improve moldability and flexibility, but also function well as hydrolysis accelerators as described above.
[0040] The total content of the first additives in the first layer is 0.1% by mass or more and 5.0% by mass or less with respect to the first layer. When the total content of the first additives is 0.1% by mass or more, hydrolysis of the biodegradable resin can be promoted and the decomposition rate can be increased. When the total content of the first additives is 5.0% by mass or less, bleeding out of the additives can be effectively prevented. From the same viewpoint, the total content of the first additives is preferably 0.1% by mass or more and 4.0% by mass or less, and more preferably 0.2% by mass or more and 3.0% by mass or less.
[0041] 1-1-4.Other ingredients The first layer may further contain other components other than those mentioned above, if necessary. Examples of other components include other resins other than those mentioned above, other plasticizers, lubricants, colorants, antioxidants, ultraviolet absorbers, coupling agents, flow improvers, flame retardants, foaming agents, antistatic agents, etc. These can be used alone or in combination of two or more. Among these, antioxidants are preferred.
[0042] Examples of the antioxidant include hindered phenol-based, hindered amine-based and phosphite-based antioxidants.
[0043] The total amount of the other components may be within a range that does not impair the effects of the present invention, and may be 2.0% by mass or less, preferably 0.1% by mass or more and 1.5% by mass or less, based on the first layer. When the total amount of the other components is within the above range, bleeding out and the like can be further reduced.
[0044] 1-1-5.Physical properties The thickness of the first layer depends on the application, but is preferably, for example, 10 μm to 2000 μm, more preferably 50 μm to 500 μm. When the thickness of the first layer is 10 μm or more, the decomposition rate of the biodegradable laminate can be increased, and the biodegradability after use can be increased. When the thickness of the first layer is 2000 μm or less, the decomposition rate of the biodegradable laminate is unlikely to be excessively increased, and the mechanical strength during use is unlikely to be impaired.
[0045] 1-2. Second layer The second layer includes a biodegradable resin, an inorganic powder, and at least one selected from the group consisting of an isocyanate compound, an epoxy compound, and a carbodiimide compound as a second additive, and has a faster decomposition rate than the first layer.
[0046] The biodegradable resin and inorganic powder contained in the second layer may be the same as those listed as the biodegradable resin and inorganic powder contained in the first layer. The content and mass ratio range of the biodegradable resin and inorganic powder in the second layer may be the same as the content and mass ratio range of the biodegradable resin and inorganic powder in the first layer.
[0047] The biodegradable resin and inorganic powder contained in the second layer may be the same as or different from the biodegradable resin and inorganic powder contained in the first layer. For example, from the viewpoint of further improving production efficiency and interlayer adhesion, it is preferable that the biodegradable resin and inorganic powder contained in the second layer are the same as the biodegradable resin and inorganic powder contained in the first layer.
[0048] The content of the inorganic substance powder contained in the second layer may be the same as or different from the content of the inorganic substance powder contained in the first layer. For example, the higher the content of the inorganic substance powder, the faster the hydrolysis rate. Therefore, the content of the inorganic substance powder in the first layer may be higher than the content of the inorganic substance powder in the second layer.
[0049] 1-2-1. Second additive The second additive is one or more selected from the group consisting of an isocyanate compound, an epoxy compound, and a carbodiimide compound. These components can function as hydrolysis inhibitors. Specifically, when the biodegradable resin is hydrolyzed, a free carboxylic acid is generated. The isocyanate group, epoxy group, carbodiimide group, or the like of the above components can react quickly with the free carboxylic acid, and therefore can inhibit the hydrolysis of the biodegradable resin.
[0050] (Isocyanate compounds) The isocyanate compound is a compound having an isocyanate group in one molecule, and is preferably an alkylene diisocyanate or cycloalkylene diisocyanate having 2 to 20 carbon atoms, and more preferably having 3 to 12 carbon atoms.
[0051] Examples of alkylene diisocyanates include 1,2-ethylene diisocyanate; tetramethylene diisocyanates such as 1,2-tetramethylene diisocyanate, 1,3-tetramethylene diisocyanate, and 1,4-tetramethylene diisocyanate; hexamethylene diisocyanates such as 1,2-hexamethylene diisocyanate, 1,3-hexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, 1,5-hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, and 2,5-hexamethylene diisocyanate; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, and lysine diisocyanate.
[0052] Examples of the cycloalkylene diisocyanate include isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; and 4,4'-dicyclohexylmethane diisocyanate.
[0053] Among these, from the viewpoint of higher reactivity with free carboxylic acids, alkylene diisocyanates having 3 to 12 carbon atoms are preferred, and 1,6-hexamethylene diisocyanate is more preferred.
[0054] (Epoxy compounds) An epoxy compound is a compound having an epoxy group in one molecule. Examples of such epoxy compounds include epoxidized oils, epoxy group-containing polymers containing structural units derived from monomers having epoxy groups, and reaction products of polyhydric alcohols (e.g., glycerol, sorbitol, pentaerythritol, polyethylene glycol, etc.) and halogen-containing epoxides such as epichlorohydrin. Among them, epoxy group-containing polymers are preferred from the viewpoint of containing many epoxy groups in one molecule and making it easier to suppress hydrolysis.
[0055] The epoxy group-containing polymer may be a copolymer containing a structural unit derived from (meth)acrylate and a structural unit derived from glycidyl (meth)acrylate. In this specification, the term "(meth)acrylate" refers to acrylate, methacrylate, or both.
[0056] Examples of (meth)acrylates include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, etc. Examples of glycidyl (meth)acrylates include glycidyl methyl (meth)acrylate, glycidyl ethyl (meth)acrylate, etc.
[0057] The copolymer may further contain structural units derived from other copolymerization monomers. Examples of other copolymerization monomers include ethylenically unsaturated carboxylic acids other than those mentioned above (e.g., (meth)acrylic acid, maleic acid, itaconic acid); styrenes (e.g., styrene, α-methylstyrene, vinyltoluene), and the like.
[0058] The content of the structural unit derived from glycidyl (meth)acrylate is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more, based on the total structural units constituting the copolymer. The higher the content of the structural unit derived from glycidyl (meth)acrylate, the more free carboxylic acid can be captured, and the slower the hydrolysis rate can be.
[0059] The epoxy equivalent can be, for example, 150 g / equivalent or more and 3000 g / equivalent or less, preferably 200 g / equivalent or more and 500 g / equivalent or less. If the epoxy equivalent is below the upper limit, the number of epoxy groups in one molecule is large, so that the hydrolysis rate can be slowed down.
[0060] The weight average molecular weight of the epoxy group-containing polymer can be, for example, 2000 to 25000, preferably 3000 to 8000. When the weight average molecular weight of the epoxy group-containing polymer is equal to or higher than the lower limit, the heat resistance can be improved, and when it is equal to or lower than the upper limit, the moldability can be improved. The weight average molecular weight can be measured in terms of polystyrene by gel permeation chromatography.
[0061] Specific examples of epoxy group-containing polymers include copolymers of styrene, (meth)acrylic acid ester, and glycidyl (meth)acrylate. Commercially available products include Joncryl ADR series (manufactured by BASF), such as Joncryl ADR 4368.
[0062] (Carbodiimide compounds) A carbodiimide compound is a compound having a carbodiimide group (-N=C=N-) in one molecule. The carbodiimide compound may be a monocarbodiimide compound having one carbodiimide group in one molecule, or a polycarbodiimide compound having two or more carbodiimide groups in one molecule.
[0063] Examples of the monocarbodiimide compound include dicyclohexylcarbodiimide, bis-2,6-diisopropylphenylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, and the like.
[0064] Examples of the polycarbodiimide compound include aromatic dicarbodiimide compounds such as p-phenylene-bis-o-triylcarbodiimide, p-phenylene-bis-p-chlorophenylcarbodiimide, and ethylene-bis-diphenylcarbodiimide; aliphatic polycarbodiimide compounds such as poly(4,4'-dicyclohexylmethanecarbodiimide); and aromatic polycarbodiimide compounds such as poly(N,N'-di-2,6-diisopropylphenylcarbodiimide) and poly(1,3,5-triisopropylphenylene-2,4-carbodiimide).
[0065] Commercially available carbodiimide compounds may be used, including B2756 manufactured by Tokyo Chemical Industry Co., Ltd., Carbodilite LA-1 manufactured by Nisshinbo Chemical Inc., and Stabaxol P, Stabaxol P400, and Stabaxol I manufactured by Rhein Chemie.
[0066] Among these, from the viewpoint of further improving heat resistance, aromatic carbodiimide compounds are preferred, and from the viewpoint of further improving the hydrolysis suppression effect, aromatic polycarbodiimide compounds are more preferred.
[0067] The number average molecular weight of the polycarbodiimide compound is not particularly limited, but can be, for example, 1000 to 30000, preferably 2000 to 20000, more preferably 3000 to 15000. If the number average molecular weight is 1000 or more, the heat resistance is higher, so that not only is the compound itself less likely to decompose during compounding, but also the damage to the biodegradable resin can be reduced. If the number average molecular weight is 30000 or less, the dispersibility in the resin is less likely to be impaired. The number average molecular weight can also be measured by the same method as above.
[0068] (Common matters) The second layer may contain only one of the above-mentioned components as the second additive, or may contain two or more of them. Among them, from the viewpoint of a high hydrolysis suppression effect, it is preferable that the second layer contains a carbodiimide compound.
[0069] The total content of the second additives in the second layer is 0.1% by mass or more and 5.0% by mass or less with respect to the second layer. When the total content of the second additives is 0.1% by mass or more, hydrolysis of the biodegradable resin in the second layer can be suppressed, and the decomposition rate can be slowed. When the total content of the second additives is 5.0% by mass or less, not only can the decomposition rate be suppressed from becoming too slow, but also a decrease in moldability can be effectively prevented. From the same viewpoint, the total content of the second additives is preferably 0.1% by mass or more and 4.0% by mass or less, and more preferably 0.2% by mass or more and 0.5% by mass or less.
[0070] The second layer may further contain other components as described above, similar to the first layer. For example, the second layer may further contain a lubricant from the viewpoint of further improving moldability.
[0071] Examples of lubricants include higher aliphatic alcohols such as stearyl alcohol and cetyl alcohol; higher fatty acids such as lauric acid, stearic acid, oleic acid, and behenic acid; and metal salts of higher fatty acids such as calcium stearate, magnesium stearate, zinc stearate, and calcium hydroxystearate.
[0072] The content of the lubricant in the second layer can be, for example, 2.0% by mass or less, preferably 0.1% by mass or more and 1.0% by mass or less. By setting the content of the lubricant within the above range, friction between the components in the resin composition can be further reduced, and moldability can be further improved.
[0073] 1-2-2.Physical properties The thickness of the second layer is not particularly limited, but is preferably 1 μm or more and 500 μm or less, and more preferably 5 μm or more and 100 μm or less. When the thickness of the second layer is 1 μm or more, the decomposition rate of the biodegradable laminate can be slowed down, and the mechanical strength during use can be increased. When the thickness of the second layer is 500 μm or less, the decomposition rate of the biodegradable laminate is unlikely to be excessively slowed, and the biodegradability after use is unlikely to be impaired.
[0074] The thickness ratio of the first layer to the second layer (first layer:second layer) may be set within a range suitable for the application. When the biodegradable laminate is used, for example, as a seedling pot or an agricultural mulch film, the thickness ratio of the first layer to the second layer is preferably 99:1 to 70:30, and more preferably 95:5 to 80:20. When the thickness ratio of the second layer is increased, the decomposition rate of the biodegradable laminate becomes slower, and the mechanical strength during use can be better maintained. When the thickness ratio of the second layer is decreased, the decomposition rate of the biodegradable laminate tends to become faster, and the biodegradability after use can be improved.
[0075] The number of first layers and second layers is not particularly limited, and each may be only one layer, or may be two or more layers.
[0076] 1-3. Other layers The biodegradable laminate may further include other layers as necessary. Examples of the other layers include other resin layers and paper substrates.
[0077] 1-4. Properties of biodegradable laminates The total thickness of the biodegradable laminate is not particularly limited, but is preferably 100 μm or more and 2500 μm or less, and more preferably 500 μm or more and 1000 μm or less. If the total thickness of the biodegradable laminate is 100 μm or more, the mechanical strength of the biodegradable laminate can be further increased. If the total thickness of the biodegradable laminate is 2500 μm or less, the moldability and biodegradability are less likely to be impaired.
[0078] The shape of the biodegradable laminate is not particularly limited, and may be any of a sheet, bag, container, and tube shape.
[0079] 1-5. Manufacturing method of biodegradable laminate The biodegradable laminate can be produced by a known method.
[0080] For example, in the case of a sheet-shaped biodegradable laminate, the biodegradable laminate can be obtained by a method of dry laminating (thermocompression bonding) a monolayer sheet corresponding to the first layer and a monolayer sheet corresponding to the second layer, or by a method of co-extruding a resin composition corresponding to the first layer and a resin composition corresponding to the second layer.
[0081] In the case of a biodegradable laminate having a three-dimensional shape, the biodegradable laminate can be obtained by vacuum forming or press molding a sheet-like biodegradable laminate. Alternatively, the biodegradable laminate can be obtained by multi-layer co-extrusion molding, multi-layer blow molding, multi-layer injection molding (e.g., two-color molding), etc.
[0082] 2. Molded products and applications The molded article according to this embodiment contains, at least in part, the biodegradable laminate.
[0083] The molded article can be used for various applications such as packaging materials, agricultural materials, civil engineering and construction materials, etc. Among them, the molded article can be preferably used for materials that are difficult to recover or reuse after use, such as agricultural mulch films, seedling pots, bags (e.g., plastic shopping bags, garbage bags, heavy-duty bags, etc.), bottles (e.g., beverage bottles), etc.
[0084] Agricultural mulch films are films that cover a part of the soil surface to keep the soil moisture and temperature constant, promote the growth of agricultural crops, and prevent the growth of weeds by blocking sunlight, and are used with one side in contact with the soil. When the above-mentioned molded product is used as an agricultural mulch film, it is preferable that the first layer is disposed on the side in contact with the soil. This allows the first layer to be quickly decomposed by the moisture in the soil after use.
[0085] In addition, when the molded article is used in a seedling pot, a bag, or a bottle, it is preferable that the second layer is disposed on the inside of the molded article and the first layer is disposed on the outside of the molded article, thereby making it possible to stably retain contents containing a large amount of moisture.
[0086] For example, in a seedling pot, by making the inner layer the second layer and the outer layer the first layer, neither the inner nor outer layer decomposes much during the period when the seed is growing, and the rigidity can be maintained. On the other hand, when the pot is planted in soil after growth, the outer layer decomposes in a short period of time, leaving only the inner layer, and then it crumbles easily due to a significant decrease in rigidity. The finely crushed inner layer gradually decomposes, making it easy to dispose of.
[0087] The heavy-duty bag is also used as a packaging material for contents with a high moisture content, such as leaf mold. As described above, by making the inner layer of the heavy-duty bag the second layer and the outer layer the first layer, the contents can be stably held during use and can be rapidly biodegraded after use. In order to make it easier to impart sealing properties to the bag, the content of the inorganic substance powder in the inner layer may be less than the content of the inorganic substance powder in the outer layer.
[0088] The biodegradable laminate can also be used for purposes other than those mentioned above, for example, as a food container. In that case, the molded article preferably has an inner layer, an intermediate layer, and an outer layer. It is preferable that a second layer is disposed on the inner layer and the outer layer, and a first layer is disposed on the intermediate layer. It is preferable that the thickness of the inner layer and the outer layer is thinner than the thickness of the intermediate layer.
[0089] As a result, when the molded body is exposed to ultraviolet light or wind and rain in an external environment after use, the fragmentation progresses, exposing many cross sections, and the intermediate layer is quickly decomposed. The inner layer and the outer layer are sufficiently thin compared to the intermediate layer, so that they are fragmented and the specific surface area increases, and they are decomposed. In addition, in the application of food containers, it is preferable that the content of inorganic substance powder in the inner layer and the outer layer is less than the content of inorganic substance powder in the intermediate layer, or that no inorganic substance powder is contained. EXAMPLES
[0090] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.
[0091] 1. Material Preparation 1-1. Biodegradable resin PBAT: Polybutylene adipate terephthalate (MFR 4.0g / 10min: 190℃ 2.16kg, melting point 115~125℃)
[0092] <Melt point measurement method> The melting point was determined as the top temperature of the highest melting point peak on the crystal melting curve obtained by melting the above sample by heating it from 20°C to 190°C at a rate of 10°C / min under a nitrogen stream using a differential scanning calorimeter.
[0093] 1-2.Inorganic substance powder Heavy calcium carbonate powder (Takehara Chemical Industry Co., Ltd., WS-2200, average particle size 1.3 μm)
[0094] <Average particle size of inorganic powder> The specific surface area was calculated from the measurement results of the specific surface area by the air permeability method according to JIS M-8511 using a specific surface area measuring device "SS-100 type" manufactured by Shimadzu Corporation.
[0095] 1-3. First additive (hydrolysis promoter) Additive 1-1: Glycerol acetate fatty acid ester Additive 1-2: Acetyl tributyl citrate
[0096] 1-4. Second additive (hydrolysis inhibitor) Additive 2-1: Joncryl ADR 4468 (BASF, polyepoxide compound) Additive 2-2: Hexamethylene diisocyanate (aliphatic diisocyanate compound) Additive 2-3: Stabaxol P (manufactured by Rhein Chemie, poly(N,N'-bis(2,6-diisopropylphenyl)carbodiimide), number average molecular weight 3000-4000) (carbodiimide compound)
[0097] 1-5. Other additives Lubricant-1: SL-800 (Riken Vitamin Co., Ltd., higher alcohol fatty acid ester) Lubricant-2: Metal soap Antioxidant-1: AO-20 (ADEKA Corporation, hindered phenol-based antioxidant) Antioxidant-2: 2112 (ADEKA Corporation, phosphite-based antioxidant)
[0098] 2. Preparation of resin composition 2-1. Preparation of resin compositions A-1 to A-4 for the first layer The materials were fed into a co-rotating twin-screw kneading extruder "HK-25D" (φ25 mm, L / D=41, manufactured by Parker Corporation) in the proportions shown in Table 1, and strands were extruded at a cylinder temperature of 180°C. After that, the strands were cooled and cut to produce pellets.
[0099] 2-2. Preparation of Resin Compositions B-1 to B-8 for Second Layer The materials were fed into a co-rotating twin-screw kneading extruder "HK-25D" (φ25 mm, L / D=41, manufactured by Parker Corporation) in the proportions shown in Table 2, and strands were extruded at a cylinder temperature of 180°C. After that, the strands were cooled and cut to produce pellets.
[0100] 2-3. Preparation of resin compositions C-1 and C-2 As shown in Tables 1 and 2, pellets were prepared in the same manner as for resin compositions A-1 and B-1, except that neither the first additive nor the second additive was added.
[0101] 2-4.Evaluation of hydrolysis rate 1) The pellet-shaped resin composition prepared above was molded by inflation molding to obtain a test piece having a thickness of 20 μm. The elongation of the obtained test piece was measured according to JIS K7161-1:2014 (ISO 527-1:2012). 2) The test pieces were stored in a thermostatic chamber at 70°C and 90% RH for two weeks. 3) The elongation retention rate was calculated from the elongation rate before and after storage according to the following formula. Elongation retention rate (%) = [1-{(elongation rate before storage - elongation rate after storage) / elongation rate before storage}] x 100
[0102] The results were evaluated according to the following criteria. The results are shown in Tables 1 and 2. 5: Elongation is maintained at 80% or more and hydrolysis is hardly occurring (hydrolysis rate is very slow) 4: The elongation rate is between 60% and 80%, and the hydrolysis rate is slow. 3: The elongation rate is between 40% and 60%, and the hydrolysis rate is normal. 2: The elongation rate is between 20% and 40%, and the hydrolysis rate is fast. 1: The elongation retention rate is less than 20% and the hydrolysis rate is very fast.
[0103] [Table 1]
[0104] [Table 2]
[0105] As shown in Table 1, the resin compositions A-1 to A-4 containing the first additive have a higher hydrolysis rate than the resin composition C-1 not containing the first additive, while as shown in Table 2, the resin compositions B-1 to B-8 containing the second additive have a lower hydrolysis rate than the resin composition C-2 not containing the second additive.
[0106] In particular, it is found that the use of Additive 2-3 (carbodiimide compound) as the second additive has a higher effect of suppressing the hydrolysis rate than Additive 2-1 (aliphatic diisocyanate compound) or Additive 2-2 (polyepoxide compound) (Comparison of resin compositions B-1, B-3, and B-7 in Table 2).
[0107] It is also seen that in the first layer, when the amount of inorganic substance powder is increased, the hydrolysis rate becomes faster even if the amount of the first additive is small (compare resin compositions A-2 and A-4 in Table 1).It is also seen that in the second layer, when the amount of inorganic substance powder is decreased, the amount of the second additive is small and the hydrolysis rate becomes slower (compare resin compositions B-5 and B-8 in Table 2).
[0108] 3. Preparation and evaluation of seedling pots [Tests 1-14] (Preparation of seedling pots) The resin composition for the first layer and the resin composition for the second layer were extruded by a two-layer T-die extruder to obtain a laminated sheet with a total thickness of 500 μm in the combination and thickness shown in Table 3. The obtained laminated sheet was molded by a vacuum molding machine so that the outer layer and the inner layer were the layers shown in Table 3, to obtain a seedling pot.
[0109] [Test 15] A seedling pot was obtained in the same manner as in Test 1, except that a single-layer sheet was produced using only the resin composition A-1 for the first layer.
[0110] [Test 16] A seedling pot was obtained in the same manner as in Test 1, except that a single-layer sheet was produced using only the resin composition B-7 for the second layer.
[0111] [Test 17] A seedling pot was obtained in the same manner as in Test 1, except that the resin composition C-2 was used instead of the resin composition for the second layer.
[0112] (evaluation) The obtained seedling pots were used for the following evaluation.
[0113] (1) Stability of the seedling pots during seedling raising The seedling pots thus obtained were filled with about 80% of their capacity using culture soil, tomato seeds were planted in them, and the pots were then maintained in a greenhouse. After three months, the state of the pots was observed and evaluated according to the following criteria. AA: Almost no destruction, and seedlings can be kept stable. A: No destruction and the seedlings can be kept stable. B: Some damage is observed, but the seedlings can still be retained. C: Destruction or delamination occurs, and the seedlings cannot be held stably.
[0114] (2) Evaluation of biodegradability after transplantation The seedling pots after the evaluation in (1) above were directly transplanted into a field, and the condition after 3 months was observed and evaluated according to the following criteria. AA: The seedling pot has decomposed to the extent that it no longer retains its original shape, and the seedlings have grown sufficiently and have spread their roots to the soil outside the seedling pot. A: Some of the seedling pots remain undecomposed, but this does not affect the growth of the seedlings. B: About half of the seedling pot remains undecomposed, but this does not hinder the growth of the seedlings. C: The seedling pots are barely decomposed, and the seedlings' roots have not yet reached the soil outside the pots, so they are not growing.
[0115] The evaluation results of tests 1 to 17 are shown in Table 3.
[0116] [Table 3]
[0117] As shown in Table 3, the seedling pots of Tests 1 to 14, which contained a laminated sheet having a first layer containing a predetermined amount of a first additive and a second layer containing a predetermined amount of a second additive, had good stability during seedling raising and also had good biodegradability after transplanting.
[0118] In particular, it can be seen that using the first layer as the outer layer and the second layer as the inner layer provides a better balance between stability during seedling growth and biodegradability after transplanting than using the second layer as the outer layer and the first layer as the inner layer (Comparison between Tests 7 and 13).
[0119] In addition, it can be seen that using a carbodiimide compound as the second additive has a greater effect in reducing the decomposition rate and provides greater stability during seedling cultivation than using an isocyanate compound or an epoxy compound (Comparison between Tests 1, 3, and 7, and Comparison between Tests 9 to 11).
[0120] It is also clear that a moderately thin thickness ratio of the second layer can adequately increase the stability of the pot while maintaining biodegradability (Comparison between Tests 7 and 12).
[0121] In contrast, the seedling pot of Test 16, which did not have the first layer, was found to have low biodegradability after transplantation. Also, the seedling pots of Tests 15 and 17, which did not have the second layer, were found to have low stability during seedling growth. [Industrial Applicability]
[0122] According to the present invention, it is possible to provide a biodegradable laminate that can be adjusted to a desired decomposition rate even if it contains a large amount of inorganic substance powder. A molded article containing such a laminate can be suitably used as a material that is impossible or difficult to recover or reuse after use, such as a seedling pot or an agricultural mulch film.
Claims
1. A biodegradable laminate having a first layer and a second layer, Each of the first layer and the second layer contains a biodegradable resin and an inorganic substance powder in a mass ratio of 70:30 to 10:90, The first layer further contains one or more first additives selected from the group consisting of glycerin acetate fatty acid ester and acetyl tributyl citrate in an amount of 0.1% by mass or more and 5.0% by mass or less; The second layer further contains one or more second additives selected from the group consisting of an isocyanate compound, an epoxy compound, and a carbodiimide compound, in an amount of 0.1% by mass to 5.0% by mass. Biodegradable laminate.
2. Each of the first layer and the second layer contains the biodegradable resin and the inorganic substance powder in a mass ratio of 70:30 to 30:
70. The biodegradable laminate according to claim 1.
3. The biodegradable resin includes one or more biodegradable resins selected from the group consisting of polylactic acid, polyhydroxybutyrate, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), polycaprolactone, polybutylene succinate, polyethylene succinate, polymalic acid, polyglycolic acid, polydioxanone, poly(2-oxetanone), polybutylene adipate terephthalate (PBAT), and polybutylene succinate adipate (PBSA); The biodegradable laminate according to claim 1.
4. The biodegradable resin includes a biodegradable resin having a melting point of 170° C. or less. The biodegradable laminate according to claim 1.
5. The inorganic powder includes ground calcium carbonate powder. The biodegradable laminate according to claim 1.
6. The average particle size of the ground calcium carbonate powder is 0.7 μm or more and 6.0 μm or less. The biodegradable laminate according to claim 5.
7. The biodegradable laminate according to any one of claims 1 to 6, Molded body.
8. The molded body is an agricultural mulch film in which one surface is in contact with soil, The first layer is disposed on the side that contacts the soil. The molded article according to claim 7.
9. The molded body is a seedling pot, a bag or a bottle, The second layer is disposed on the inside of the molded body, The first layer is disposed on the outer side of the molded body. The molded article according to claim 7.
Citation Information
Patent Citations
Polylactic acid based resin laminated film, its manufacturing method, and its easy degrading discarding method
JP2007216541A
film
JP2014005330A
Biodegradable film
JP2016208849A
Polymer mixture for barrier film
JP2017505831A
Resin composition and molded article
JP6916571B1